2018
DOI: 10.15446/agron.colomb.v36n3.74149
|View full text |Cite
|
Sign up to set email alerts
|

Radish (Raphanus sativus L.) morphophysiology under salinity stress and ascorbic acid treatments

Abstract: The use of saline or low-quality water in agriculture is an alternative to increasing water demand, especially in arid or semi-arid regions. However, the use of water with high levels of salts causes disturbances in plants, which can lead to their death; thus, alternatives to mitigate these effects are relevant in current agriculture. Currently, antioxidants are used to mitigate the effects of salts in plants, and among them ascorbic acid has been frequently mentioned. Therefore, the aim of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
2
1
0
1
Order By: Relevance
“…According to this author, their short cycle can suppress potential serious effects. Basílio et al (2018) also found a behaviour similar to that observed in our study.…”
Section: Fuzzy Model Resultssupporting
confidence: 92%
“…According to this author, their short cycle can suppress potential serious effects. Basílio et al (2018) also found a behaviour similar to that observed in our study.…”
Section: Fuzzy Model Resultssupporting
confidence: 92%
“…However, we found that 2 mM AA did not attenuate stress caused by either a water excess (W100) or a de cit (W50). These ndings were similar to those of radish plants grown under saline, where AA also did not attenuate stress effects(Basílio et al 2018;Leal et al 2019).…”
supporting
confidence: 81%
“…A previous study showed that salinity can significantly reduce the rate and final percentages of the germination and emergence of amaranth, resulting in uneven stand establishment and decreased crop yields [33]. A growth reduction was observed in the leaf of amaranth sprouts under saline conditions; such a reduction was associated with a reduction in photosynthetic pigments [34]. Agricultural productivity and quality are negatively affected by salt stress, which puts a strain on the food supply to meet the demands of a growing population [35].…”
Section: Cnps Improved Growth Parameters Of Amaranth Sprouts Under Th...mentioning
confidence: 95%